PENGARUH KUALITAS KEHIDUPAN KERJA DAN DUKUNGAN ATASAN TERHADAP KEPUASAN KERJA DAN DAMPAKNYA TERHADAP CARIER PLATEAU (STUDI PADA PNS PERANGKAT KELURAHAN SE KECAMATAN SEMARANG TENGAH) (Jurnal Mahasiswa Pasca Sarjana, 2015)
The purpose of this study was to examine the effect of the quality of working life and support employers to job satisfaction and to the career plateau. The use of variables in the study variables refer to the results of previous studies. This research was conducted in the village officials se PNS Central District of Semarang, Semarang, respondents who used as many as 98 employees,This study uses multiple regression analysis techniques. The research instrument used in this study to qualify the validity and reliability. This study used two equation model is to determine the effect of the quality of working life and support employers to job satisfaction, and the quality of working life, supervisor support and job satisfaction on a career plateau. The results showed that the model-1 is significantly able to explain changes in the dependent variable so that the model is eligible goodness of fit, whereas in the 2nd tinyatakan models can not account for the influence of variables on the career plateau bebsanya. Hypothesis testing results show that the quality of working life and support superiors positive effect on job satisfaction. Likewise, the quality of working life and support superiors also affect negatively to the career plateau, whereas the effect of job satisfaction affect the career plateau. The results also show that job satisfaction was not berupakan factor that mediates the effect of the quality of work life and supervisor support for career plateau, but the factor of job satisfaction have a tendency to minimize its influence on the career plateau. Keywords: quality of working life, supervisor support, job satisfaction and career plateau.